Понимание риска в уголовно- правовой науке - Корякин, И.П. (Изд-во КарГУ., 2009)
Мақалада əр түрлі көзқарастардың негізінде тəуекелдің жəне түрлі формадағы тəуекелдің заңшығарушы-нормативтік бекітілу түсінігі қарастырылған. Жүргізілген зерттеудің нəтижесінде қылмыстық-құқықтық ғылымдағы кейбір сəйкессіздіктер туралы қорытынды шығарылған. In given clause the understanding of risk on the basis of the various points of view and legislative normative fastening of risk in its various forms is considered. Given clause is a part of complex research of risk and its separate interpretation in various branches of the right. As a result of carried out research conclusions about some discrepancies in criminally-legal science are received.